Pengaruh Pengawasan Kerja, Budaya Kerja, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan (Studi Kasus Pada Karyawan Pt. Nippon Indosari Corpindo Tbk Kabupaten Pasuruan) - Dana Sefrina Sulviadi; Afi Rahmat Slamet; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study was used to analyze the effect of work supervision, work culture, work environment, and job satisfaction on employee work productivity at PT Sindsali Pasluen Regency. The sample for this survey was 71 employees who answered. The method used in this study is multiple linear regression with first-order data analysis using the SPSS For Windows application. Based on the results of the research and discussion in the previous chapter, the following conclusions can be drawn:The test results simultaneously show that the variables of work supervision, work culture, work environment and job satisfaction have an effect on employee productivity. The partial test results show that the Work Supervision Variable has no effect on Employee Work Productivity. The partial test results show the variables of work culture, work environment and job satisfaction have a positive effect on employee productivity.Keywords: Work Supervision, Work Culture, Work Environment, Job Satisfaction, Employee Productivity